Update breast cancer 2020 part 3 - early breast cancer = Update Mammakarzinom 2020 Teil 3–frühes Mammakarzinom - Huober, Jens; Schneeweiss, Andreas; Hartkopf, Andreas D.; Müller, Volkmar; Lux, Michael P.; Janni, Wolfgang; Ettl, Johannes; Belleville, Erik; Thill, Marc; Fasching, Peter A.; Kolberg, Hans-Christian; Schulmeyer, Carla E.; et al. (Geburtshilfe und Frauenheilkunde, 2020)
The treatment of patients with early breast cancer has always been characterised by escalation by new therapies and de-escalation through identification of better treatment regimens or introduction of better tools to estimate prognosis. Efforts in some of these areas in the last few years have led to solid data. The results of the large studies of de-escalation through use of multi-gene tests are available, as are the results of some studies that investigated the new anti-HER2 substances T-DM1 and pertuzumab in the early treatment situation. Several large-scale studies examining the role of CDK4/6 inhibitors will soon be concluded so innovations can be anticipated in this area also. This review article will summarise and classify the results of the latest publications.
Gesehen am 12.02.2021